A regulação como propulsora de práticas de controle interno na saúde suplementar - Jácome, Marília Augusta Raulino (2018)
The present research has as its main objective to analyze the influence of the economic regulation in the adoption of internal control practices in the organizations of the supplementary health market of the Northeast Region of Brazil. To that end, the active participation of the Health Plan Operators (HPO) was sought through an instrument composed of assertions that describe internal control practices, based on the framework of COSO ICIF (2013). The surveyed sample was formed by 43 HPO in the Northeast region, which corresponds to 53,75% of the universe, and the participants were financial, account or internal audit managers, which answered to a questionnaire based on the five-points Likert scale. From the application of a quantitative and qualitative methodology, including the KruskalWallis test for the analysis of the questionnaire and the use of the content analysis technique for the analysis of the legislation and for the discursive responses, the results showed the existence of a connection between regulation and some internal control practices, although not involving all principles within the framework of the COSO. Regarding the reality of the internal control structures of the HPO from Northeast, it was observed that the general average concentrated in 3.70 representing a partial agreement of the respondents about the existence of internal control practices, as listed in the questionnaire. More specifically, the monitoring activities component presented statistical difference for all the listed practices, confirming the explanatory power of the HPO and ensuring the existence of direct influence in the adoption of internal control practices. About the existence of audit and internal control areas, small and medium-sized HPO still showed incipience, which has repercussions on the reduced dissemination of control culture in the HPO. Regarding the subordination of the internal audit, at a minimum level, the positioning is given directly in relation to the Board of Directors, which impacts on the guarantee of its performance with independence. Concerning the influence of regulation on the adoption of internal control practices of the HPO, 95% of the respondents agreed on this existence, however, in a detailed way, the respondents indicated other aspects related to regulation, such as compliance, sustainability and its punitive character. In addition, 9% of the respondents stated that there is insufficient of regulation in relation to internal controls, suggesting then the creation of specific regulations for HPO’s controls. Corroborating this such affirmation, 17% pointed out that the strengthening of the structure and of the control practices may be a path towards the sustainability of the supplementary health sector. In general, results confirmed partially the assumptions of the survey, since there is influence of the regulation in the adoption of internal control practices; however, it was not possible to confirm the relation intensity to the adoption of practices when the economic regulation is connected to it, suggesting that the connection between them is not a sufficient factor for the adoption of internal control practices.